2018
DOI: 10.1080/02673843.2018.1482773
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of alcohol consumption during early adolescence: a cross-sectional study in an eastern province, Thailand

Abstract: This cross-sectional study identified and described the prevalence of alcohol consumption among early adolescents (10-14 years). The participants were 9,509 early adolescents from Chonburi province, Thailand. Of all the adolescents, 31.01% had experience with alcohol drinking, while the current drinkers were 10.94%. Girls were more likely to drink and the amount of current drinkers increased with age (p < 0.001). Adolescents living with divorced family, single parents and neither close to both of their parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Concurred with other studies, curiosity, peers, and family members seemed to considerably influence on the students' ABC behaviors [12]. In this study, alcoholic beverages seemed to be a social symbol of young people for celebration as seen in a study of Meier and colleagues [13].…”
Section: Conclusion and Recommendationsupporting
confidence: 52%
“…Concurred with other studies, curiosity, peers, and family members seemed to considerably influence on the students' ABC behaviors [12]. In this study, alcoholic beverages seemed to be a social symbol of young people for celebration as seen in a study of Meier and colleagues [13].…”
Section: Conclusion and Recommendationsupporting
confidence: 52%
“…The family is also a protective factor against substance use [9]. Substance use is one of the highest current prevalent adolescent risk behaviours and a major global public health concern [24,25]. Parents have an opportunity to play an important role in preventing their adolescent children from engaging in risky behaviour and promote positive behaviours [26].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the ndings showed that alcohol consumption is common in adolescents, which was also found in the studies of Benjet et al ( 10), Kittipichai et al (11), and Getachew et al (12). In a study of Thai adolescents, Luecha et al (9) found that 31.01% of adolescents aged 10 to 14 had consumed alcohol at least once. In a study by Ting et al ( 22) on 11 to 12-year-old Taiwanese adolescents, alcohol consumption was reported at 48% in this group.…”
Section: Discussionmentioning
confidence: 51%
“…Alcohol consumption is very common in adolescents. A study in Thailand, done on adolescents aged 10-14 evaluated 9509 people, found 30.01% of the adolescents with the experience of alcohol consumption, adolescents whose parents were divorced or neither of their parents lived with them, had a higher chance of alcohol consumption (9). Another study of 3005 adolescents, 12-17 years old, in Mexico found that 59% of adolescents had experienced alcohol consumption, which was signi cantly associated with increasing age, low parental supervision, and dropout rates (10).…”
Section: Introductionmentioning
confidence: 99%